Application of the Problem-based Learning Model to Improve the Class V Elementary Student Learning Outcomes - Sitorus, Regina; Silaban, Patri Janson; Raja, Bogor Lumban; Ambarwati, Nova Florentina; Sitepu, Anton (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2024)
This study aims to improve student learning outcomes on the theme of heat and its transfer to the sub-theme of temperature and heat by applying the Problem-based Learning model for class V of SD Negeri 091585 AFDELING 7 DOSIN. The research type is Classroom Action Research. The research subjects involved 24 class V students. Based on the research results, it shows that there is an increase in student learning outcomes by implementing the Problem-based Learning model. This can be seen from the increase in student learning outcomes. Of the initial test (pretest), the student learning results were obtained before implementing the Problem-based Learning model. There were three people who completed it with a percentage of 12.5% while 21 people did not complete it with a percentage of 87.5% and an average of 37.95. In the first cycle, the observations of teacher activities were obtained at 52% while observations of student activities were obtained at 50%, there were 11 students who completed their learning outcomes with a percentage of 45.83% and 13 students who did not complete it with a percentage of 54.17%, and with an average value of 59.95. In cycle II, teacher activity observations were obtained at 88% while student activity observations were obtained at 90%. There were 19 students who completed their learning outcomes with a percentage of 79.17% and five students who did not complete it with a percentage of 20.82% with an average value of 73.45. This shows that there is a significant positive influence from the use of the Problem-based Learning model on student learning outcomes in theme heat and its transfer in class V at SD Negeri 091585 AFDELING 7 DOSIN in the academic year 2022/2023.